Exposição a violência interpessoal e associação com consumo de drogas lícitas em adultos: resultados da pesquisa nacional de saúde, 2019 - Silva, Eduardo Paixão (2023)
Introduction: Adults who are victims of Interpersonal Violence (IV) may have an association with chronic alcohol and tobacco use. However, the manifestation of this link can vary considerably based on gender and the frequency of exposure to these situations. This scenario remains largely unexplored, particularly in developing countries. Aim: To assess the associations between acute and chronic exposures to IV (physical, psychological, and sexual) with abusive alcohol consumption and smoking, separately for male and female adults. Methods: Cross-sectional study, secondary analysis with 72,597 participants aged 18 to 64, from the National Health Survey (PNS). Explanatory variables of interest included self-reported physical, sexual, and psychological exposures to IV in the last 12 months, categorized as: none, single, and multiple times. Dependent variables were abusive alcohol consumption and smoking. All analyses were stratified by gender as a proxy for sex. The magnitudes of associations and their 95% confidence intervals between each exposure and outcomes were estimated using Poisson regression with robust variance. Sequential adjustments were made for age, race/skin color, marital status and sexual orientation, education, and income. Results: The majority of the study population was composed of women (52.46%), aged 35 to 44, with a predominance of brown-skinned individuals. Most respondents had completed high school and had an income of up to 2 minimum wages, were single, and identified as heterosexual. Men showed higher frequencies of abusive alcohol consumption and smoking compared to women. After adjusting for all covariates, men exposed to physical, psychological (once or multiple times), and sexual violence (only once) were associated with abusive alcohol consumption and smoking (p <0.05). In addition, women exposed to any form of violence, whether single or multiple times, were associated with abusive alcohol consumption (p <0.05). However, only women exposed to physical violence (both single and multiple times) and psychological violence (only multiple times) remained related to smoking (p <0.05). Interestingly, any frequency of sexual violence did not remain associated with smoking. Conclusion: IV was more common among women and strongly linked to alcohol abuse, especially in cases of physical and psychological violence. There was no association between sexual violence and smoking in women. Among men, any form of violence (physical, psychological, or sexual) is related to alcohol abuse and smoking. No gender differences were found in associations with physical and psychological violence, highlighting the complexity of the relationships between gender, violence, and risky health behaviors in the Brazilian public health context.